RESEARCH OF THE SELF POLLUTION BY THE PERIPHYTON COMMUNITY AT THE DOWNSTREAM OF A DAM - SHIRATORI, Minoru; SHIMADA, Yoshikazu; KITTA, Ryuichi; SATO, Rui; KOZUKI, Yasunori; MURAKAMI, Hitoshi (Doboku Gakkai Ronbunshuu G, 2008)
This study was performed to understand the actual conditions of self pollution at the downstream of a dam and discusse its mechanism. When periphyton communities at the downstream of a dam were compared with communities at the upstream of a dam, the differences were especially remarkable during a summer time. At the upstream site, the communities were formed which were dominated cyanobacteria and a little biomass. At the downstream site, the diatom predominated communities were formed and the biomass were significantly much than the periphyton at the upstream site. In addition, at the downstream site, the phenomenon that a part of periphyton community detached and floated in the water were observed. These results suggested that the organic matter produced by periphyton were accumulated on the reverbed and loaded to the stream water. It was guessed that the self pollution at the downstream site were occurred because of not only a decline of flood frequency but also a decline of a grazing pressure by the fish.